2016
DOI: 10.1016/j.nbd.2015.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Increased responses in the somatosensory thalamus immediately after spinal cord injury

Abstract: Spinal cord injury (SCI) involves large-scale deafferentation of supraspinal structures in the somatosensory system, producing well-known long-term effects at the thalamo-cortical level. We recently showed that SCI provokes immediate changes in cortical spontaneous and evoked responses and here, we have performed a similar study to define the immediate changes produced in the thalamic ventro-postero-lateral nucleus (VPL) that are associated with the forepaw and hindpaw circuits. Extracellular electrophysiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 38 publications
2
38
0
Order By: Relevance
“…LFP recordings of forepaw activity stimulated at 0.5 Hz in the VPL by Alonso-Calvino et al (2016) had an amplitude around 250 μV, a similar amplitude to the 266 AE 71 μV observed here. At 20 Hz stimulation frequency the amplitude of the evoked potential recorded decreased to 168 AE 51 μV.…”
Section: Do Recorded Signals From Cortex and Thalamus Match The Litersupporting
confidence: 85%
“…LFP recordings of forepaw activity stimulated at 0.5 Hz in the VPL by Alonso-Calvino et al (2016) had an amplitude around 250 μV, a similar amplitude to the 266 AE 71 μV observed here. At 20 Hz stimulation frequency the amplitude of the evoked potential recorded decreased to 168 AE 51 μV.…”
Section: Do Recorded Signals From Cortex and Thalamus Match The Litersupporting
confidence: 85%
“…Future work should expand on the molecular mechanisms of this cortical plasticity, establishing the role of pre-synaptic and post-synaptic processes as well as the possible contribution of astrocytes and neuron-glia interaction in the cortical reorganization observed here. Overall, even though subcortical plasticity is likely to have contributed to the observed functional recovery (Kambi et al, 2014; Alonso-Calviño et al, 2016), our results suggest that at least part of the plasticity induced by our therapies after spinal cord injury is genuinely cortical.…”
Section: Discussionmentioning
confidence: 70%
“…SCI induces cellular and molecular events via both primary and secondary injury cascades (Davis et al, 1996; Alonso-Calvino et al, 2016). This cascade process leads to inflammatory reactions, neuronal apoptosis, and reactive astrogliosis, which may cause impaired regeneration, tissue loss, and functional disabilities (Chen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…These areas were diminished in the 1-W SCI group, wherein expression times were also significantly delayed. The delayed activating optical signals might be resulted from reduced populations of surviving neurons and increased demyelination after SCI (Alonso-Calvino et al, 2016; Chen et al, 2016). However, improved activating optical signals 4 weeks after SCI may have reflected spontaneous recovery, such as newly formed neuronal reorganization and neuroplasticity of the remaining neuronal synapses in the adjacent injury site (Murray et al, 2011; He et al, 2017).…”
Section: Discussionmentioning
confidence: 99%